Premières données sur la phénologie du Pigeon ramier Columba palumbus dans la région de Souk Ahras, Nord-Est de l’Algérie - GUELLATI, K; MENAA, M; KAOUACHI, A; TOUARFIA, M; REBBAH, A. C; DJOUAMAA, A; MAAZI, M.C. (My University, 2022)
This work was carried out between 2015 to 2020 and aimed to understand the ecology of the Common Wood Pigeon Columba palumbus and to integrate our results in the process of species management and conservation strategies within the forest areas of the Souk Ahras region. During our study, a significant density of the Common Wood Pigeon was observed in the different forest landscapes of our study area. The most important abundance was recorded in 2018 in the forest of Ouled Bechih with a maximum density of 5 500 individuals. We noted also an important density of this species in the forest of Djebel Zaarouria with a maximum density of 1 800 individuals. The study of the reproductive status of the Common Wood Pigeon using the point count IPA method revealed that the Boussessou forest and the Zaarouria forest revealed the most important reproductive indices. The forest of Boussessou has the higher mean of IPA with 4.14 pairs and the forest of Zaarouria has an average of 3.88 pairs.